The Trouble with Shopping: Discourses, Practices and Pedagogies of the Consumer-Citizen - Kaela Jubas (Adult Education Research Conference, 2006)
In this paper, I begin with an outline of modern citizenship and a review of feminist and other critical analyses of this concept. I then discuss the role of consumption as a marker of citizenship. The paper closes with the prospect of understanding shopping as a potential process of learning about the links between consumption, citizenship and globalization.
Keywords: Citizenship; consumption; globalization; informal adult learning